Pengaruh Model Pembelajaran Discovery Learning terhadap Kemampuan Berpikir Kritis Siswa pada Materi Virus - Rizka Rakhmahwati Nurjanah; Yudi Rinanto; Baskoro Adi Prayitno (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2019)
The purpose of this research is to know the effect of discovery learning model towards critical thinking ability about viruses of x grade students at SMA Negeri 8 Surakarta in Academic Year 2018/ 2019. The research was a quasi-experimental. The research design was used Pre test-Post test Non-Equivalent Control Group Design. The population of this research was 5 classes of X grade students at SMA Negeri 8 Surakarta in Academic Year 2018/ 2019. Sampling techniques used cluster sampling that chose X MIPA 4 grade with 35 students as the control group and X MIPA 1 grade with 36 students as experiment group. The control group applying varied lectures method and the experiment group applying discovery learning model. The technique of collecting data was test methods with 7 essay questions developed by the researcher. The essay questions were valid with validity value above 0,361 and reliable with reliability value 0,663. The hypothesis was analyzed by analysis of covariance (ANACOVA) using SPSS 19 with the significance level of 0,05. This research concluded that the discovery learning model affected significantly the critical thinking ability about viruses of X grade students at SMA Negeri 8 Surakarta in Academic Year 2018/2019.